Axial-flux synchronous machines compared with different stator structures for use in working [Porównanie struktur stojana maszyny synchroniczny o strumieniu osiowym] - (:unkn) unknown (My University, 2012)
In this study, three different stator topologies were investigated and compared utilizing 3D magnetic analysis, analytical calculations, and experimental studies. These stator structures are torus iron core: There have been far fewer studies based on slotless stator torus axial-flux permanent magnets (TAFPM-NS). Comparisons of simulated and measured values on prototype machines are also presented to validate the analyses.
Keywords: Electric generators; Finite element analysis (FEA); Torus axial flux permanent magnet machines (TAFPM)